KOMPOSISI DAN STRUKTUR VEGETASI ARBORETUM UNIVERSITAS RIAU SEBAGAI PENYIMPAN CADANGAN KARBON UNTUK PENGEMBANGAN MODUL MATA KULIAH PENDIDIKAN LINGKUNGAN - Furqan, Cashter; Wulandari, Sri; ', Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the composition, structure, and carbonstock of vegetation in Riau University Arboretum and to develop module in naturalenvironment concept for environmental education courses. Conducted from November2015 until January 2016. This study conducted in 2 step i.e. (1) Vegetation analysis andcarbon stock estimation; (2) Module development. The methods to collect data is usingsurvey and the observation took place in Riau University Arboretum. Sampling locationare determine using purposive random sampling by considering vegetation condition,environment, and topographic. Module is developed using ADDIE model. Parameter inthis study are vegetation analysis, biomass, and carbon estimation. Vegetation in RiauUniversity Arboretum consist of 25 family, 44 species, and 604 individual with mediumcategory (2,94) for diversity. Hevea brasiliensis is the species with highest importancevalue index (74,05%). Total of biomass and carbon stock in study location are 2,23ton/ha and 1,12 ton C/ha. Module that developed from outcome of the study is in validcategory (4,1) and limited test shows that the module in very good category (89,3).Key Word : Riau University Arboretum, carbon stock, module